FEATURES OF ATTRACTING HIGHLY SKILLED MIGRANTS: A COMPARATIVE ANALYSIS OF THE UNITED STATES AND THE UNITED KINGDOM (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2025)
Countries are realizing the billion-dollar question regarding innovation and productivity is highly skilled migrants, fuelling the global race for the best in show. The United States and the United Kingdom have been among the top destinations for skilled migrants due to their strong economy world-class research institutions and job opportunities. The paper will be a comparative analysis and literature review of the variables that are attractive to highly skilled migrants in these countries, considering migration trends, policy environments, and economies and outcomes. This refers to using data on human mobility to determine driving forces in migration decisions of where they choose to live, such as economic opportunities, quality of life, and the policy incentives in that location. The research shows that both countries have been effective in attracting highly skilled migrants, although they face continuing obstacles—including visa constraints, credential recognition and integration challenges. The overall conclusion of the study is that the U.S. and the UK's attractiveness to global talent can be enhanced through an appropriate mix of targeted migration policies, effective integration and policy coherence. Overcoming these challenges will enable both countries to maximize the economic and social contributions of skilled migrants, facilitating ongoing growth and innovation in an ever-competitive global environment.